Manipulasi peristiwa Israk Mikraj dalam karya sastera arab dan barat: satu analisis terhadap Al-Maqamah Al-Iblisiyah, Al-Tawabi' Wa Al-Zawabi', Risalat Al-Ghufran dan The Divine Comedy - Ahmad H.Osman, Rahmah; Nasir, Mohd Shahrizal (Penerbit Universiti Sains Malaysia Pulau Pinang, 2011)
The Isra' and Mi'raj (the night journey and ascension of Prophet Muhammad) is considered, in Islam, a symbol of the greatness of Allah. This divine experience of the Prophet, which contains a thousand and one wisdoms and miracles, is very significant in Islam and Islamic history. Yet without a strong conviction, it is not perceivable to be true. This article is an analysis of the manipulation of the Isra' and Mi'raj in several Arabic and Western literary works which make reference to the event, namely al-Maqamah al-Iblisiyah (The Maqama of Iblis), al-Tawabi' wa al-Zawabi' (The Treatise of Familiar Spirits and Demons), Risalat al-Ghufran (The Epistle of Forgiveness) and The Divine Comedy. The aim is to reveal some of the issues that emerge as a direct result of the manipulation of the Isra' and Mi'raj in these works. The existence of the manipulation of the Isra' and Mi'raj in the literary works will indicate that the heavenly incident has to some degree influenced the development of Arabic and Western literatures. If it does exist, it is important that the truth of the Isra' and Mi'raj is protected from any form of denigration that offends Islam and its followers. Nevertheless, this should not be an obstacle where creativity in literary work is concerned.